East-West Coast differences in total electron content over the continental US - Zhang, Shun-Rong; Foster, John C.; Coster, Anthea J.; Erickson, Philip J. (Geophysical research letters, 2011)
Total electron content (TEC) measurements made by a network of dense GPS receivers over the continental US are used to investigate ionospheric longitudinal differences. We find that the evening TEC is substantially higher on the US east coast than on the west, and vice versa for the morning TEC; the longitudinal difference displays a clear diurnal variation. Through an analysis of morning‐evening variability in the east‐west TEC difference, minimum variability is found to coincide with the longitudes of zero magnetic declination over the continental US. We suggest that these new findings of longitudinal differences in ionospheric TEC at midlatitudes are caused by the longitudinal difference in magnetic declination combined with the effects of thermospheric zonal winds which are subject to directional reversal over the course of a day. This study indicates that longitudinal variations in TEC measurements contain critical information on thermospheric zonal winds. The proposed declination‐zonal wind mechanism may also provide a new insight into longitude/UT changes at midlatitudes on a global scale, as well as into some geospace disturbances. Key Points US East‐West Coast differences in TEC up to 100%, varying with local time Morning‐evening variability minimum near zero magnetic dec Varying magnetic dec over US, combined with zonal wind effects